FARGO-360: a multi-disciplinary survey of practice and perspectives on provision of care for patients with frailty presenting with gynecological cancers in the UK and Ireland. Issue 7 (9th May 2022) - Wan, Yee-Loi Louise; Cass, Gemma; Collins, Anna; Adishesh, Meera; Addley, Susan; Baker-Rand, Holly; Bharathan, Rasiah; Blake, Dominic; Beirne, James; Canavan, Lisa; Dilley, James; Fitzgibbon, Gary; et al.
Abstract : Objectives: Frailty has been associated with worse cancer-related outcomes for people with gynecological cancers. However, the lack of clear guidance on how to assess and modify frailty prior to instigating active treatments has the potential to lead to large variations in practice and outcomes. This study aimed to evaluate current practice and perspectives of healthcare practitioners on the provision of care for patients with frailty and a gynecological cancer. Methods: Data were collected via a questionnaire-based survey distributed by the Audit and Research in Gynecological Oncology (ARGO) collaborative to healthcare professionals who identified as working with patients with gynecological malignancies in the United Kingdom (UK) or Ireland. Study data were collected using REDCap software hosted at the University of Manchester. Responses were collected over a 16 week period between January and April 2021. Results: A total of 206 healthcare professionals (30 anesthetists (14.6%), 30 pre-operative nurses (14.6%), 51 surgeons (24.8%), 34 cancer specialist nurses (16.5%), 21 medical/clinical oncologists (10.2%), 25 physiotherapists/occupational therapists (12.1%) and 15 dieticians (7.3%)) completed the survey. The respondents worked at 19 hospital trusts across the UK and Ireland. Frailty scoring was not routinely performed in 63% of care settings, yet the majority of practitioners reported modifying their practice when providing and deciding on care for patients with frailty. Only 16% of organizations surveyed had a dedicated pathway for assessment and management of patients with frailty. A total of 37% of respondents reported access to prehabilitation services, 79% to enhanced recovery, and 27% to community rehabilitation teams. Conclusion: Practitioners from all groups surveyed considered that appropriate training, dedicated pathways for optimization, frailty specific performance indicators and evidence that frailty scoring had an impact on clinical outcomes and patient experience could all help to improve care for frail patients.